Hydrogen Index determination for the well-log ES-1 drilled at the Espírito Santo basin (western South Atlantic) for the Late Cretaceous - Thiago Pereira dos Santos; Fellippe Roberto Alves Bione; Igor Martins Venancio; M C Bernardes; Andre L Belem; Luana P Lisboa; Daniel R Franco; Rut A Díaz; Manuel Moreira; Noele F Leonardo; Igor V Souza; André L D Spigolon; et al. (PANGAEA, 2022)
HI derives from Rock-Eval pyrolysis using 100 mg of grounded and powdered rock within a Rock-Eval 6 device.
In: Santos, TP et al. (2022): Late Cretaceous cyclostratigraphy for the subtropical western South Atlantic, Espírito Santo Basin [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.944599